DNA Computing Technique to Solve Vertex Coloring Problem - Hasudungan, Rofilde; Rohani, Abu Bakar (2013)
DNA computing or well known as molecular computing is computing technique using DNA molecule to store information and using biochemistry operation as computational tool to manipulate string in DNA strand to produce the result. Lipton point out massive parallelism and storage capacity make this convenient to solve combinatorial problems. In this paper we proposed DNA based computer to solve vertex coloring problem where in this paper we proposed DNA encoding and computational procedure inspired by greedy algorithm to generate all possible solutions to coloring a graph.